CFROI valuation : a total system approach to valuing the firm - Madden, Bartley J. (Butterworth-Heinemann, 1999)
What generates shareholder value? How can it be evaluated? How can it influence investment decisions and corporate strategy? Cash Flow Return On Investment answers all these questions by detailing the pioneering financial research carried out by HOLT Value Associates, the leading consultancy in the field. Read this book if you want to find out what really drives the wealth generation in any business, allowing you to pick which equities will succeed and which strategic initiatives are destined for high returns. The CFROI model is an essential tool for professionals working in finance and corpor.